THE USE OF TPS STRATEGY COMBINED WITH KAHOOT! IN TEACHING READING - Wahyumunika, Ni Luh Putu; Ratminingsih, Ni Made; Suprianti, G.A.P (Language and Education Journal Undiksha, 2021)
Students’ reading interest influenced students’ reading comprehension. Thus, they needed a strategy and media in reading. This study aimed to find out the effect of the implementation of the TPS strategy combined with Kahoot! on students reading comprehension. This research was experimental. The research design was post-test only control group design. The data were analyzed using descriptive and inferential statistical analysis. The result showed the mean score of the experimental group was 69.33, while the mean score of the control group was 74.67. The result t observed was higher than t critical (2.004 > -1.116) and (2.004 > -1.152). It indicated that accepted the null hypothesis. It concluded that there was no significant effect of the implementation of the TPS strategy combined with Kahoot! of students reading comprehension. The TPS strategy can use for different skills.